Super-hydrophobic polymer film as well as preparation method and application thereof

By combining porous polymer matrix film layer and long-chain alkyl silicon particles in polymer film to form a superhydrophobic polymer film with micro-nano composite structure, the performance degradation of existing films when treating organic pollutants and colloidal substance wastewater is solved. The problem of this achieves efficient and durable oil-water separation effect.

CN119425407APending Publication Date: 2025-02-14JIANGSU YANGNONG CHEMICAL GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411730402.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When treating wastewater containing organic pollutants and colloidal substances, existing polymer films are easily adsorbed/blocked, resulting in reduced performance and increased energy consumption, making it difficult to meet the water purification needs under harsh conditions.

Method used

The porous polymer matrix film layer is used to recombine with silicon particles with long-chain alkyl groups to form a superhydrophobic polymer film in a micro-nano composite form, which improves the wear resistance, strength and superhydrophobic properties of the film.

Benefits of technology

It significantly improves the separation efficiency and durability of the superhydrophobic polymer film, can maintain efficient separation performance under harsh conditions, reduces the adhesion between oil and water, and ensures a fast and clean separation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425407A_ABST
    Figure CN119425407A_ABST
Patent Text Reader

Abstract

The invention provides a super-hydrophobic polymer film and a preparation method and application thereof. The super-hydrophobic polymer film comprises a porous polymer matrix film layer and silicon particles with long-chain alkyl on the porous polymer matrix film layer. The preparation method comprises the following steps: (1) mixing a pore-forming agent, an oxygen-containing polymer and a first organic solvent to obtain a spinning solution, and spinning the spinning solution to obtain a porous precursor membrane; (2) mixing silicate ester, polyalkyl ethoxysilane, a second organic solvent and the porous precursor film, and performing ultrasonic treatment to obtain an ultrasonic treated material; and (3) mixing a precipitant and the ultrasonic-treated material, carrying out a precipitation reaction, and sequentially cleaning and freeze-drying an obtained second precursor film to obtain the super-hydrophobic polymer film. According to the invention, high membrane separation flux and high separation efficiency gt can be obtained; and the super-hydrophobic polymer film with acid and alkali resistance has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of separation membranes, and in particular to a super-hydrophobic polymer membrane and a preparation method and application thereof. Background Art

[0002] Epichlorohydrin (Epichlorohydrin, ECH) is an important organic chemical raw material and intermediate, mainly used in the production of epoxy resins, plasticizers, medicines, pesticides, surfactants and adhesives and other products, with good market prospects. At present, a large number of studies have begun to catalyze the synthesis of epichlorohydrin by direct oxidation of allyl chloride and hydrogen peroxide using TS-1 molecular sieve as a catalyst.

[0003] The hydrogen peroxide method has the advantages of mild reaction conditions, low energy consumption, simple process, and high atomic utilization, but there is still a problem of low utilization of by-products in wastewater. The hydrogen peroxide method produces epichlorohydrin, and each ton of epichlorohydrin produced will produce 1.0 to 1.5 tons of wastewater, the COD of the wastewater is 5000 to 30000 ppm, and the main organic matter in the wastewater is 0.5 to 1.0% glycerol, 0.1 to 0.2% 3-chloro-1,2-propylene glycol (abbreviated as monochloropropylene glycol), 0.2-0.3% 1-chloro-3-methoxy-2-propanol, 0.1-0.2% methanol, and the acidity is 0.1 to 0.4%.

[0004] CN101293882A obtains a methanol-rich liquid phase through extraction and separation, and obtains 3-chloropropylene and methanol through rectification, but it also produces a certain amount of rectification wastewater. There are still a lot of intermediate products (such as glycerol and glycerol monomethyl ether) in this wastewater. If it cannot be recovered, the cost of three wastes treatment will be significantly increased, and the economic efficiency of hydrogen peroxide process epichlorohydrin will be reduced.

[0005] To this end, researchers have developed various separation technologies, such as distillation, media filtration, membrane, ion exchange, precipitation and electrosorption. Among them, membrane technology is the simplest strategy, with relatively low energy consumption, simple operation, and effective separation of oil and water.

[0006] Therefore, ECH distillation wastewater is usually treated with polymer membranes, in which the membrane concentrated oil after membrane treatment undergoes multi-effect evaporation, decoking, and distillation to obtain C3 alcohol ether and glycerol by-products. The membrane concentrated water can meet the emission requirements after simple biochemical treatment, reducing the cost of pollution removal and further improving economy and environmental protection.

[0007] However, these polymer membranes are highly susceptible to adsorption / blocking by organic pollutants and colloidal substances, and are contaminated and corroded, resulting in structural distortion, performance degradation, and increased energy consumption.

[0008] Therefore, oil / water separation membranes with simultaneously high separation performance, excellent chemical stability, and antifouling properties must be developed to address the challenges of water purification under harsh conditions. Summary of the invention

[0009] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a super-hydrophobic polymer membrane and a preparation method and application thereof, which utilizes a porous polymer matrix membrane layer to be composited with silicon particles having a long-chain alkyl group, which not only improves the wear resistance and strength of the membrane, but also forms a structure with a micro-nano composite morphology to increase the surface roughness, thereby significantly improving the super-hydrophobic performance.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a super-hydrophobic polymer membrane, comprising a porous polymer matrix membrane layer, and silicon particles having long-chain alkyl groups on the porous polymer matrix membrane layer.

[0012] It is worth noting that the super-hydrophobic polymer film provided by the present invention has the following characteristics: first, a porous polymer matrix film layer is adopted, which not only enhances the flexibility of the film and increases the specific surface area of ​​the film, but also its porous structure can provide conditions for the loading of silicon particles with long-chain alkyl groups. The silicon particles with long-chain alkyl groups can be firmly connected to the surface of the porous polymer matrix film layer, which, on the one hand, improves the wear resistance and strength of the polymer film, and on the other hand, forms a structure with a micro-nano composite morphology to increase the surface roughness, thereby significantly improving the super-hydrophobic performance.

[0013] Preferably, the porous polymer matrix membrane layer is made of an oxygen-containing polymer.

[0014] The present invention preferably uses oxygen-containing polymers as the porous polymer matrix film layer. The presence of groups such as hydroxyl groups or acid groups can improve the interface between inorganic and organic substances, thereby improving the mechanical and thermal properties of the porous polymer matrix film layer.

[0015] Preferably, the material of the porous polymer matrix membrane layer includes any one of polyvinyl alcohol, polyethylene imine, polylactic acid, polyacrylic acid or polyethylene glycol, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of polyvinyl alcohol and polyethylene imine, a combination of polylactic acid and polyethylene imine, a combination of polyvinyl alcohol and polylactic acid, and a combination of polyacrylic acid and polyethylene glycol.

[0016] Preferably, the specific surface area of ​​the super hydrophobic polymer film is 30 to 80 m 2 / g, for example, 30m 2 / g, 36m 2 / g, 42m 2 / g, 47m 2 / g, 53m 2 / g, 58m 2 / g, 64m 2 / g, 69m 2 / g, 75m 2 / g or 80m 2 / g, etc., but are not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0017] Preferably, the thickness of the superhydrophobic polymer film is 0.4-1 μm, for example, it can be 0.4 μm, 0.47 μm, 0.54 μm, 0.6 μm, 0.67 μm, 0.74 μm, 0.8 μm, 0.87 μm, 0.94 μm or 1 μm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0018] Preferably, the content of silicon particles with long-chain alkyl groups in the superhydrophobic polymer film is 5-10%, for example, it can be 5%, 5.6%, 6.2%, 6.7%, 7.3%, 7.8%, 8.4%, 8.9%, 9.5% or 10%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0019] Preferably, the contact angle of the superhydrophobic polymer film with water is 155-165°, for example, it can be 155°, 157°, 158°, 159°, 160°, 161°, 162°, 163°, 164° or 165°, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0020] Preferably, the porosity of the porous polymer matrix membrane layer is 60-90%, for example, it can be 60%, 64%, 67%, 70%, 74%, 77%, 80%, 84%, 87% or 90%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0021] Preferably, the long-chain alkyl group has 12 to 18 carbon atoms, for example, 12, 13, 14, 15, 16, 17 or 18 carbon atoms.

[0022] Preferably, the particle size of the silicon particles is 20 to 100 nm, for example, it can be 20 nm, 29 nm, 38 nm, 47 nm, 56 nm, 65 nm, 74 nm, 83 nm, 92 nm or 100 nm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0023] The present invention has no special requirements for the preparation method of the superhydrophobic polymer membrane described in the first aspect, as long as it can meet the technical characteristics of the superhydrophobic polymer membrane described in the first aspect. It is preferably prepared by the preparation method of the superhydrophobic polymer membrane described in the second aspect of the present invention, which has better membrane separation performance.

[0024] In a second aspect, the present invention provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0025] (1) mixing a pore-forming agent, an oxygen-containing polymer and a first organic solvent to obtain a spinning solution, and spinning the spinning solution to obtain a porous precursor membrane;

[0026] (2) mixing silicate, polyalkylethoxysilane, a second organic solvent and a porous precursor film, and performing ultrasonic treatment to obtain an ultrasonic post-material;

[0027] (3) mixing a precipitant and the ultrasonic post-material to carry out a precipitation reaction, and the obtained second precursor film is sequentially washed and freeze-dried to obtain a super-hydrophobic polymer film.

[0028] The preparation method of the super-hydrophobic polymer film provided by the present invention has the following obvious characteristics: firstly, a pore-forming agent is used to form holes with controllable pore size in the fiber to enhance the flexibility of the film and increase its specific surface area; then, an organic matter with a long-chain alkyl group is formed through grafting and hydrolysis condensation reaction between silicate, polyalkylethoxysilane and oxygen-containing groups, and finally a precipitant is added for precipitation to form silicon particles with a long-chain alkyl group. The silicon particles with a long-chain alkyl group can significantly improve the wear resistance and strength of the polymer film, and at the same time significantly improve the super-hydrophobic performance.

[0029] Preferably, the polymer in step (1) is any one of polyvinyl alcohol, polyethylene imine, polylactic acid, polyacrylic acid or polyethylene glycol, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of polyvinyl alcohol and polyethylene imine, a combination of polylactic acid and polyethylene imine, a combination of polyvinyl alcohol and polylactic acid, and a combination of polyethylene glycol and polyacrylic acid, preferably polyvinyl alcohol and / or polylactic acid.

[0030] Preferably, the pore-forming agent comprises any one of zinc acetate, ammonium chloride or benzoic acid or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of zinc acetate and ammonium chloride, a combination of benzoic acid and ammonium chloride, and a combination of zinc acetate and benzoic acid, preferably zinc acetate and / or ammonium chloride.

[0031] Preferably, the first organic solvent comprises any one of N,N-dimethylformamide, dimethyl sulfoxide, o-dichlorobenzene or toluene, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of N,N-dimethylformamide and dimethyl sulfoxide, a combination of o-dichlorobenzene and dimethyl sulfoxide, a combination of N,N-dimethylformamide and o-dichlorobenzene, a combination of toluene and o-dichlorobenzene, preferably N,N-dimethylformamide and / or dimethyl sulfoxide.

[0032] Preferably, the mass ratio of the pore former to the oxygen-containing polymer is 1:(1.5-10), for example, it can be 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, etc., preferably 1:(4-8).

[0033] Preferably, the usage ratio of the oxygen-containing polymer to the first organic solvent is 0.04 to 0.1 g / mL, for example, it can be 0.04 g / mL, 0.05 g / mL, 0.06 g / mL, 0.06 g / mL, 0.07 g / mL, 0.08 g / mL, 0.08 g / mL, 0.09 g / mL, 0.1 g / mL or 0.1 g / mL, but is not limited to the listed values. Other values ​​not listed within this range are also applicable, preferably 0.05 to 0.065 g / mL.

[0034] Preferably, the mixing in step (1) is performed under stirring.

[0035] Preferably, the stirring temperature is 60-90°C, for example, it can be 60°C, 64°C, 67°C, 70°C, 74°C, 77°C, 80°C, 84°C, 87°C or 90°C, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 70-80°C.

[0036] Preferably, the stirring time is 2 to 6 hours, for example, 2 hours, 2.5 hours, 2.9 hours, 3.4 hours, 3.8 hours, 4.3 hours, 4.7 hours, 5.2 hours, 5.6 hours or 6 hours, but is not limited to the listed values. Other values ​​not listed in this range are also applicable, preferably 3 to 4 hours.

[0037] Preferably, the applied voltage for spinning in step (1) is 10 to 20 KV, for example, it can be 10 KV, 12 KV, 13 KV, 14 KV, 15 KV, 16 KV, 17 KV, 18 KV, 19 KV or 20 KV, but is not limited to the listed values. Other values ​​not listed within the range are also applicable, preferably 15 to 18 KV.

[0038] Preferably, the spinning feed rate is 0.4 to 1.2 mL / h, for example, it can be 0.4 mL / h, 0.5 mL / h, 0.6 mL / h, 0.7 mL / h, 0.8 mL / h, 0.9 mL / h, 1 mL / h, 1.1 mL / h, 1.2 mL / h or 1.2 mL / h, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 0.7 to 0.9 mL / h.

[0039] Preferably, the spinning distance is 13 to 24 cm, for example, it can be 13 cm, 15 cm, 16 cm, 17 cm, 18 cm, 20 cm, 21 cm, 22 cm, 23 cm or 24 cm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable, preferably 17 to 20 cm.

[0040] Preferably, the spinning in step (1) is followed by drying to obtain a dry porous precursor membrane.

[0041] The present invention has no special requirements for the spinning process, and can be carried out using a spinning process familiar to those skilled in the art, for example, it may include: after setting the applied voltage, feed speed, and spinning distance, pouring the spinning solution into a syringe at room temperature for feeding, and spinning.

[0042] Preferably, the drying temperature is 60-100°C, for example, it can be 60°C, 65°C, 69°C, 74°C, 78°C, 83°C, 87°C, 92°C, 96°C or 100°C, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable, preferably 70-80°C.

[0043] Preferably, the drying time is 8 to 24 hours, for example, it can be 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 17 hours, 19 hours, 21 hours, 23 hours or 24 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable, preferably 12 to 18 hours.

[0044] Preferably, the silicate in step (2) comprises any one of tetraethyl orthosilicate, tetramethyl silicate or tetrabutyl silicate, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of tetraethyl orthosilicate and tetramethyl silicate, a combination of tetrabutyl silicate and tetramethyl silicate, and a combination of tetraethyl orthosilicate and tetrabutyl silicate, preferably tetraethyl orthosilicate.

[0045] Preferably, the polyalkylethoxysilane includes any one of dodecylethoxysilane, hexadecylethoxysilane or octadecylethoxysilane, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of dodecylethoxysilane and hexadecylethoxysilane, a combination of octadecylethoxysilane and hexadecylethoxysilane, and a combination of dodecylethoxysilane and octadecylethoxysilane, preferably dodecylethoxysilane and / or hexadecylethoxysilane.

[0046] Preferably, the second organic solvent comprises ethanol.

[0047] Preferably, the mass ratio of silicate: polyalkylethoxysilane: ethanol is 1: (1.2-2.6): (48-80), preferably 1: (1.5-2.2): (60-72). The mass fraction of polyalkylethoxysilane can be, for example, 1.2, 1.4, 1.6, 1.7, 1.9, 2, 2.2, 2.3, 2.5 or 2.6, etc., but is not limited to the listed values, and other values ​​not listed in this range are also applicable; the mass fraction of ethanol can be, for example, 48, 52, 56, 59, 63, 66, 70, 73, 77 or 80, etc., but is not limited to the listed values, and other values ​​not listed in this range are also applicable.

[0048] Preferably, the mass ratio of the sum of the silicate, polyalkylethoxysilane and ethanol in step (2) to the porous precursor film is 145 to 225:1, for example, it can be 145:1, 154:1, 163:1, 172:1, 181:1, 190:1, 199:1, 208:1, 217:1 or 225:1, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0049] Preferably, the power of the ultrasonic treatment is 100-500 W, for example, 100 W, 145 W, 189 W, 234 W, 278 W, 323 W, 367 W, 412 W, 456 W or 500 W, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0050] Preferably, the ultrasonic treatment time is 10 to 60 min, for example, 10 min, 16 min, 22 min, 27 min, 33 min, 38 min, 44 min, 49 min, 55 min or 60 min, but is not limited to the listed values. Other values ​​not listed within the range are also applicable, preferably 30 to 45 min.

[0051] Preferably, the ratio of the precipitant to the silicate in step (3) is (2.2-8.5):1, for example, 2.2:1, 2.3:1, 2.4:1, 3.1:1, 3.8:1, 4.5:1, 5.2:1, 5.8:1, 6.5:1, 7.2:1, 7.9:1 or 8.5:1, but is not limited to the listed values. Other values ​​not listed within the range are also applicable, preferably (4.4-6.2):1.

[0052] Preferably, the precipitant is aqueous ammonia.

[0053] Preferably, the pH of the ammonia water is 10-12, for example, 10, 10.3, 10.5, 10.7, 10.9, 11.2, 11.4, 11.6, 11.8 or 12, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0054] Preferably, the precipitation reaction time is 6 to 16 hours, for example, it can be 6 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, but is not limited to the listed values. Other values ​​not listed in this range are also applicable, preferably 8 to 12 hours.

[0055] Preferably, the freeze-drying temperature is 0-40°C, for example, it can be 0°C, 5°C, 9°C, 14°C, 18°C, 23°C, 27°C, 32°C, 36°C or 40°C, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 10-30°C.

[0056] Preferably, the freeze-drying time is 2 to 8 hours, for example, it can be 2 hours, 2.7 hours, 3.4 hours, 4 hours, 4.7 hours, 5.4 hours, 6 hours, 6.7 hours, 7.4 hours or 8 hours, but is not limited to the listed values. Other values ​​not listed in this range are also applicable, preferably 4 to 6 hours.

[0057] Preferably, the cleaning comprises cleaning with ethanol and water in sequence.

[0058] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0059] (1) mixing a pore-forming agent, an oxygen-containing polymer and a first organic solvent, and stirring at 60 to 90° C. for 2 to 6 hours to obtain a spinning solution, spinning the spinning solution, applying a voltage of 10 to 20 KV, a feed rate of 0.4 to 1.2 mL / h, and a spinning distance of 13 to 24 cm to obtain a porous precursor film, and then drying at 60 to 100° C. for 8 to 24 hours to obtain a dry porous precursor film;

[0060] The mass ratio of the pore-forming agent to the oxygen-containing polymer is 1:(1.5-10), and the amount ratio of the oxygen-containing polymer to the first organic solvent is 0.04-0.1 g / mL.

[0061] (2) mixing silicate, polyalkylethoxysilane, a second organic solvent and a porous precursor film, and ultrasonically treating the mixture for 10 to 60 minutes at a power of 100 to 500 W to obtain an ultrasonic material; the mass ratio of silicate: polyalkylethoxysilane: ethanol is 1: (1.2 to 2.6): (48 to 80), and the mass ratio of the sum of silicate, polyalkylethoxysilane and ethanol to the porous precursor film is 145 to 225: 1;

[0062] (3) Mixing ammonia water with a pH of 10 to 12 and the ultrasonic material in a ratio of ammonia water to silicate of (2.2 to 8.5):1, and performing a precipitation reaction for 6 to 16 hours to obtain a second precursor film; the second precursor film is washed three times with ethanol and water in sequence, and then freeze-dried at 0 to 40°C for 2 to 8 hours to obtain a super hydrophobic polymer film.

[0063] In a third aspect, the present invention provides an application of a superhydrophobic polymer membrane in oil-water separation, wherein the superhydrophobic polymer membrane is the superhydrophobic polymer membrane described in the first aspect, and / or the superhydrophobic polymer membrane is a superhydrophobic polymer membrane prepared by the preparation method of the superhydrophobic polymer membrane described in the second aspect.

[0064] The super-hydrophobic polymer membrane provided by the present invention has high flux and high acid and alkali resistance, and has good application prospects in the field of oil-water separation.

[0065] Preferably, the superhydrophobic polymer membrane is used in oil-water separation in the purification of ECH methanol distillation wastewater.

[0066] Compared with the prior art, the present invention has at least the following beneficial effects:

[0067] (1) The preparation method of the super-hydrophobic polymer membrane provided by the present invention uses a pore-forming agent to prepare a membrane structure with controllable pore size in the fiber, thereby enhancing the flexibility and specific surface area of ​​the membrane, improving the overall performance of the membrane, and being able to be optimized according to different needs to meet the diverse industrial application needs. At the same time, a larger specific surface area also helps to increase the separation flux of the membrane, effectively improving the separation efficiency;

[0068] (2) The preparation method of the super-hydrophobic polymer membrane provided by the present invention constructs a micro-nano composite structure so that the membrane surface has excellent super-hydrophobicity, thereby greatly improving the rate and efficiency of oil-water separation, reducing the adhesion between oil and water, and ensuring a fast and clean separation process;

[0069] (3) The super-hydrophobic polymer membrane provided by the present invention can still maintain efficient separation performance after being soaked in acid and alkali, has excellent durability and stability, and reduces the replacement frequency and maintenance cost of the membrane. Under preferred conditions, the separation efficiency of the super-hydrophobic polymer membrane is above 99%, the contact angle with water is above 155°, and the separation efficiency hardly decreases after acid and alkali treatment;

[0070] (4) The super-hydrophobic polymer membrane provided by the present invention can effectively separate ECH methanol distillation wastewater. The membrane concentrated oil and membrane concentrated water can be simply treated to recover C3 alcohol ether and glycerol by-products, and the discharge conditions are met, thereby improving the economy and environmental protection of epichlorohydrin produced by hydrogen peroxide method. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 It is a transmission electron microscope image of the super-hydrophobic polymer film provided in Example 1 of the present invention.

[0072] Figure 2 This is a separation efficiency diagram of the superhydrophobic polymer membrane provided in Example 10 of the present invention for oil-water separation testing. DETAILED DESCRIPTION

[0073] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0074] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0075] Example 1

[0076] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0077] (1) 0.2 g of zinc acetate, 1.6 g of polyvinyl alcohol (molecular weight of 20,000) and 20 mL of N,N-dimethylformamide were mixed and stirred at 60° C. for 3 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 15 KV, a feed rate of 0.7 mL / h, and a spinning distance of 17 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 10 kPa and 60° C. for 12 h to obtain a dry porous precursor membrane;

[0078] (2) mixing 4.5 mL of tetraethyl orthosilicate, 7.6 mL of dodecylethoxysilane, 270 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture at a power of 200 W for 30 min to obtain an ultrasonically treated material;

[0079] (3) According to the ratio of ammonia water to tetraethyl orthosilicate of 4.44:1, 20 mL of ammonia water with a pH of 11 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 12 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 40°C for 2 hours to obtain a superhydrophobic polymer film.

[0080] The transmission electron microscopy image of the super hydrophobic polymer film prepared in this example is shown in Figure 1 ,from Figure 1 It can be seen that the surface of the superhydrophobic polymer film has obvious micro-nanoparticles, which helps the film to improve its superhydrophobicity.

[0081] Example 2

[0082] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0083] (1) 1 g of ammonium chloride, 1.5 g of polyethyleneimine (molecular weight 10,000) and 38 mL of dimethyl sulfoxide were mixed and stirred at 70° C. for 4 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 18 KV, a feed rate of 0.9 mL / h, and a spinning distance of 20 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 15 kPa and 70° C. for 18 h to obtain a dry porous precursor membrane;

[0084] (2) mixing 4.5 mL of tetraethyl orthosilicate, 6.7 mL of hexadecylethoxysilane, 320 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture for 10 min at a power of 100 W to obtain an ultrasonically treated material;

[0085] (3) According to the ratio of ammonia water to tetraethyl orthosilicate of 6.22:1, 28 mL of ammonia water with a pH of 10.5 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 8 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 30°C for 4 hours to obtain a superhydrophobic polymer film.

[0086] Example 3

[0087] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0088] (1) 0.5 g of benzoic acid, 2.0 g of polylactic acid (molecular weight 20,000) and 40 mL of toluene were mixed and stirred at 90° C. for 2 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 20 KV, a feed rate of 1.2 mL / h, and a spinning distance of 24 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 10 kPa and 80° C. for 24 h to obtain a dry porous precursor membrane;

[0089] (2) mixing 4.5 mL of tetramethyl silicate, 11.6 mL of dodecylethoxysilane, 360 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture for 60 min at a power of 300 W to obtain an ultrasonically treated material;

[0090] (3) According to the ratio of ammonia water to tetraethyl orthosilicate of 4.44:1, 20 mL of ammonia water with a pH of 12 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 10 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 10°C for 9 hours to obtain a superhydrophobic polymer film.

[0091] Example 4

[0092] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0093] (1) 0.24 g of zinc acetate, 2.4 g of polyacrylic acid (molecular weight of 10,000) and 20 mL of o-dichlorobenzene were mixed and stirred at 80° C. for 6 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 10 KV, a feed rate of 0.4 mL / h, and a spinning distance of 13 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 5 kPa and 100° C. for 8 h to obtain a dry porous precursor membrane;

[0094] (2) mixing 4.5 mL of tetrabutyl silicate, 5.4 mL of octadecylethoxysilane, 220 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture for 45 min at a power of 500 W to obtain an ultrasonically treated material;

[0095] (3) According to the ratio of ammonia water to tetrabutyl silicate of 7.78:1, 35 mL of ammonia water with a pH of 10 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 6 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 20°C for 8 hours to obtain a superhydrophobic polymer film.

[0096] Example 5

[0097] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0098] (1) 0.2 g of benzoic acid, 1.8 g of polyethylene glycol (molecular weight 20,000) and 30 mL of dimethyl sulfoxide were mixed and stirred at 70° C. for 3 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 16 KV, a feed rate of 0.8 mL / h, and a spinning distance of 18 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 10 kPa and 80° C. for 12 h to obtain a dry porous precursor membrane;

[0099] (2) mixing 4.5 mL of tetrabutyl silicate, 8.4 mL of octadecylethoxysilane, 285 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture at a power of 200 W for 30 min to obtain an ultrasonically treated material;

[0100] (3) According to the ratio of ammonia water to tetrabutyl silicate of 5.56:1, 25 mL of ammonia water with a pH of 11.5 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 8 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 40°C for 3 hours to obtain a superhydrophobic polymer film.

[0101] Example 6

[0102] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0103] (1) 0.3 g of ammonium chloride, 1.8 g of polyethylene glycol (molecular weight of 20,000) and 25 mL of o-dichlorobenzene were mixed and stirred at 80° C. for 4 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 18 KV, a feed rate of 0.8 mL / h, and a spinning distance of 19 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 10 kPa and 80° C. for 14 h to obtain a dry porous precursor membrane;

[0104] (2) mixing 4.5 mL of tetraethyl orthosilicate, 5.4 mL of hexadecylethoxysilane, 240 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture at a power of 100 W for 45 min to obtain an ultrasonically treated material;

[0105] (3) According to the ratio of ammonia water to tetrabutyl silicate of 2.67:1, 12 mL of ammonia water with a pH of 11 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 12 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 20°C for 2 hours to obtain a superhydrophobic polymer film.

[0106] Example 7

[0107] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0108] (1) 0.4 g of zinc acetate, 2.0 g of polylactic acid (molecular weight of 20,000) and 20 mL of toluene were mixed and stirred at 90° C. for 5 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 17 KV, a feed rate of 0.9 mL / h, and a spinning distance of 21 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 10 kPa and 90° C. for 16 h to obtain a dry porous precursor membrane;

[0109] (2) mixing 4.5 mL of tetraethyl orthosilicate, 6.4 mL of octadecylethoxysilane, 300 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture at a power of 300 W for 30 min to obtain an ultrasonically treated material;

[0110] (3) According to the ratio of ammonia water to tetrabutyl silicate of 6.67:1, 30 mL of ammonia water with a pH of 11 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 12 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 40°C for 2 hours to obtain a superhydrophobic polymer film.

[0111] Example 8

[0112] This embodiment provides a method for preparing a super-hydrophobic polymer film, the preparation method comprising the following steps:

[0113] (1) 0.5 g of benzoic acid, 2.4 g of polyvinyl alcohol (molecular weight 20,000) and 30 mL of N,N-dimethylformamide were mixed and stirred at 60° C. for 3 h to obtain a spinning solution, and the spinning solution was spun at an applied voltage of 20 KV, a feed rate of 1.0 mL / h, and a spinning distance of 24 cm. The spinning solution was poured into a syringe for feeding at room temperature. After the feeding was completed, the spun membrane was placed in a vacuum drying oven and dried at 10 kPa and 60° C. for 18 h to obtain a dry porous precursor membrane;

[0114] (2) mixing 4.5 mL of tetraethyl orthosilicate, 5.6 mL of hexadecylethoxysilane, 220 mL of ethanol and 1.5 g of the porous precursor film, and ultrasonically treating the mixture at a power of 400 W for 30 min to obtain an ultrasonically treated material;

[0115] (3) According to the ratio of ammonia water to tetrabutyl silicate of 2.22:1, 10 mL of ammonia water with a pH of 11 and the ultrasonic material were mixed, and a precipitation reaction was carried out for 8 hours to obtain a second precursor film; the second precursor film was washed three times with ethanol and water in sequence, and then freeze-dried at 10°C for 4 hours to obtain a superhydrophobic polymer film.

[0116] Example 9

[0117] This embodiment provides a method for preparing a super-hydrophobic polymer film. The preparation method is the same as that of Embodiment 1 except that polyvinyl alcohol is replaced by polyethylene, and the details are not described again.

[0118] Example 10

[0119] This embodiment provides a method for preparing a super-hydrophobic polymer film. The preparation method is the same as that of Example 1 except that the amount of zinc acetate added is 0.1 g, and will not be described in detail herein.

[0120] Embodiment 11

[0121] This embodiment provides a method for preparing a super-hydrophobic polymer film. The preparation method is the same as that of Example 1 except that the amount of zinc acetate added is 2 g, and will not be described in detail herein.

[0122] Example 12

[0123] This embodiment provides a method for preparing a super-hydrophobic polymer film. The preparation method is the same as that of Embodiment 1 except that dodecylethoxysilane is replaced by dodecylmethoxysilane, and the details are not described again.

[0124] Example 13

[0125] This embodiment provides a method for preparing a super-hydrophobic polymer film. The preparation method is the same as that of Embodiment 1 except that ammonia water is replaced by sodium hydroxide with the same pH value, and thus will not be described in detail herein.

[0126] Comparative Example 1

[0127] This comparative example provides a method for preparing a polymer film. The preparation method is the same as Example 1 except that step (2) and step (3) are not performed, and the details are not repeated here.

[0128] Comparative Example 2

[0129] This comparative example provides a method for preparing a polymer film. The preparation method is the same as Example 1 except that tetraethyl orthosilicate is not added, and the details are not repeated here.

[0130] Comparative Example 3

[0131] This comparative example provides a method for preparing a polymer film. The preparation method is the same as Example 1 except that dodecylethoxysilane is not added, and the details are not repeated here.

[0132] Comparative Example 4

[0133] This comparative example provides a method for preparing a polymer film. The preparation method is the same as Example 1 except that zinc acetate is not added, and the details are not repeated here.

[0134] Acid resistance test: The prepared superhydrophobic polymer membrane was immersed in 1 mol / L hydrochloric acid for 12 h, washed three times with ethanol and deionized water respectively, and freeze-dried at 40 °C for 4 h before the subsequent oil-water separation test.

[0135] Alkali resistance test: The prepared separation membrane was immersed in a 1 mol / L sodium hydroxide solution for 12 h, then washed three times with ethanol and deionized water, and freeze-dried at 40 °C for 4 h before conducting subsequent oil-water separation tests.

[0136] Oil-water separation test: ECH methanol distillation wastewater was used as the test liquid phase, which was composed of 1% glycerol, 0.2% monochloropropylene glycol, 0.2% 1-chloro-3-methoxy-2-propanol, 0.2% methanol, and the rest was pure water; the operation process was: the prepared separation membrane was fixed between two transparent containers, and 40mL of ECH methanol distillation wastewater was poured into the upper container under differential pressure at room temperature (25°C) for separation.

[0137] Permeation flux (J) and separation efficiency were calculated as follows:

[0138] J=V / (A*T)

[0139] η=(m / m0)*100%

[0140] Where V is the separation volume, A is the effective separation area, T is the separation time, and m0 and m are the oil masses before and after oil-water separation, respectively.

[0141] Taking Example 1 as an example, the oil-water separation membrane prepared in Example 1 was subjected to 20 oil-water separation experiments. After each separation process, the separation membrane was cleaned three times with ethanol and three times with distilled water, and then freeze-dried at 40°C for 4 hours for further use. The results of the 20 separations are shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the super-hydrophobic polymer membrane prepared by the present invention has excellent oil-water separation efficiency. After repeating 20 times, its separation efficiency is still stable at more than 98%, maintaining good hydrophobicity, and has a good separation effect on ECH methanol distillation wastewater.

[0142] The separation performance results of the above examples and comparative examples are shown in Table 1 below.

[0143] Table 1

[0144]

[0145]

[0146] In Table 1, “-” indicates that there is no relevant data. After the membrane provided in the comparative example was treated with acid and alkali, it was severely damaged and difficult to continue membrane separation. The following points can be seen from Table 1:

[0147] (1) It can be seen from Examples 1 to 8 that the porous super-hydrophobic polymer membrane prepared by the present invention has excellent separation performance for methanol distillation wastewater, and still exhibits excellent separation effect after acid and alkali immersion. The surface has excellent acid and alkali resistance, wherein the separation efficiency is above 99%, the contact angle with water is above 155°, and the separation efficiency hardly decreases after acid and alkali treatment.

[0148] (2) Compared with Example 9, the polyethylene in Example 9 lacks active groups (hydroxyl groups) compared with polyvinyl alcohol, which makes it difficult to graft with tetraethyl orthosilicate and dodecylethoxysilane to form micro-nano silicon particles. Compared with the membrane in Example 1, the contact angle with water is only 95°, and the separation efficiency is reduced.

[0149] (3) In Example 10, too little addition of the pore-forming agent (zinc acetate) will result in low porosity and insufficient surface roughness of the membrane, thereby affecting the superhydrophobicity of the membrane. Compared with the membrane in Example 1, the contact angle with water is 135°, and the separation efficiency is reduced. In Example 11, too much addition of the pore-forming agent (zinc acetate) will result in excessive porosity, excessively large pores, and uneven pore distribution, thereby reducing the mechanical strength and hydrophobicity of the membrane. Compared with the membrane in Example 1, the contact angle with water is 142°, and the separation efficiency is greatly reduced.

[0150] (4) The hydrolysis reaction of methoxysilane in Example 12 is relatively slow, resulting in a low degree of crosslinking of the membrane, and the organic silicon coating formed on the membrane surface is not uniform, which affects the hydrophobicity of the membrane. Compared with the membrane in Example 1, the contact angle with water is 117°, and the separation efficiency is reduced.

[0151] (5) In Example 13, sodium hydroxide was used instead of ammonia water as the precipitant, and the precipitation was too fast, and excessive hydrolysis generated too many hydrophilic groups, resulting in uneven pore structure, which affected the uniformity of the structure and superhydrophobicity. Compared with the membrane in Example 1, the contact angle with water was 126°, and the separation efficiency was reduced.

[0152] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A super hydrophobic polymer film, characterized in that: The super hydrophobic polymer film comprises a porous polymer matrix film layer and silicon particles with long-chain alkyl groups on the porous polymer matrix film layer.

2. The super-hydrophobic polymer film according to claim 1, characterized in that The material of the porous polymer matrix film layer includes any one of polyvinyl alcohol, polyethyleneimine, polylactic acid, polyacrylic acid or polyethylene glycol, or a combination of at least two thereof; Preferably, the specific surface area of ​​the super hydrophobic polymer film is 30 to 80 m 2 / g; Preferably, the thickness of the super hydrophobic polymer film is 0.4 to 1 μm; Preferably, the content of silicon particles having long-chain alkyl groups in the super-hydrophobic polymer film is 5 to 10%; Preferably, the contact angle between the superhydrophobic polymer film and water is 155-165°; Preferably, the porosity of the porous polymer matrix membrane layer is 60-90%; Preferably, the number of carbon atoms of the long-chain alkyl group is 12 to 18; Preferably, the particle size of the silicon particles is 20-100 nm.

3. A method for preparing a super-hydrophobic polymer film, characterized in that: The preparation method comprises the following steps: (1) mixing a pore-forming agent, an oxygen-containing polymer and a first organic solvent to obtain a spinning solution, and spinning the spinning solution to obtain a porous precursor membrane; (2) mixing silicate, polyalkylethoxysilane, a second organic solvent and a porous precursor film, and performing ultrasonic treatment to obtain an ultrasonic post-material; (3) mixing a precipitant and the ultrasonic post-material to carry out a precipitation reaction, and the obtained second precursor film is sequentially washed and freeze-dried to obtain a super-hydrophobic polymer film.

4. The preparation method according to claim 3, characterized in that: The polymer in step (1) is any one of polyvinyl alcohol, polyethyleneimine, polylactic acid, polyacrylic acid or polyethylene glycol, or a combination of at least two thereof, preferably polyvinyl alcohol and / or polylactic acid; Preferably, the pore-forming agent comprises any one of zinc acetate, ammonium chloride or benzoic acid or a combination of at least two thereof, preferably zinc acetate and / or ammonium chloride; Preferably, the first organic solvent comprises any one of N,N-dimethylformamide, dimethyl sulfoxide, o-dichlorobenzene or toluene or a combination of at least two thereof, preferably N,N-dimethylformamide and / or dimethyl sulfoxide; Preferably, the mass ratio of the pore former to the oxygen-containing polymer is 1:(1.5-10), preferably 1:(4-8); Preferably, the usage ratio of the oxygen-containing polymer to the first organic solvent is 0.04 to 0.1 g / mL, preferably 0.05 to 0.065 g / mL.

5. The preparation method according to claim 3 or 4, characterized in that: The mixing in step (1) is carried out under stirring; Preferably, the stirring temperature is 60 to 90°C, preferably 70 to 80°C; Preferably, the stirring time is 2 to 6 hours, preferably 3 to 4 hours.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The applied voltage for spinning in step (1) is 10 to 20 KV, preferably 15 to 18 KV; Preferably, the spinning feed rate is 0.4 to 1.2 mL / h, preferably 0.7 to 0.9 mL / h; Preferably, the spinning distance of the spinning is 13 to 24 cm, preferably 17 to 20 cm; Preferably, the spinning in step (1) is followed by drying to obtain a dry porous precursor membrane; Preferably, the drying temperature is 60-100°C, preferably 70-80°C; Preferably, the drying time is 8 to 24 hours, preferably 12 to 18 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The silicate in step (2) includes any one of tetraethyl orthosilicate, tetramethyl silicate or tetrabutyl silicate, or a combination of at least two thereof, preferably tetraethyl orthosilicate; Preferably, the polyalkylethoxysilane includes any one of dodecylethoxysilane, hexadecylethoxysilane or octadecylethoxysilane or a combination of at least two thereof, preferably dodecylethoxysilane and / or hexadecylethoxysilane; Preferably, the second organic solvent comprises ethanol; Preferably, the mass ratio of the silicate:polyalkylethoxysilane:ethanol is 1:(1.2-2.6):(48-80), preferably 1:(1.5-2.2):(60-72).

8. The preparation method according to any one of claims 3 to 7, characterized in that: The mass ratio of the sum of the silicate, polyalkylethoxysilane and ethanol to the porous precursor film in step (2) is 145 to 225:1; Preferably, the power of the ultrasonic treatment is 100 to 500 W; Preferably, the ultrasonic treatment time is 10 to 60 min, preferably 30 to 45 min.

9. The preparation method according to any one of claims 3 to 8, characterized in that: In step (3), the ratio of the precipitant to the silicate is (2.2-8.5):1, preferably (4.4-6.2):1; Preferably, the precipitant is aqueous ammonia; Preferably, the pH of the ammonia water is 10 to 12; Preferably, the precipitation reaction time is 6 to 16 hours, preferably 8 to 12 hours; Preferably, the freeze-drying temperature is 0 to 40°C, preferably 10 to 30°C; Preferably, the freeze-drying time is 2 to 8 hours, preferably 4 to 6 hours; Preferably, the cleaning comprises cleaning with ethanol and water in sequence.

10. Application of a super hydrophobic polymer membrane in oil-water separation, characterized in that: The super-hydrophobic polymer film is the super-hydrophobic polymer film according to claim 1 or 2, and / or the super-hydrophobic polymer film is a super-hydrophobic polymer film prepared by the method for preparing a super-hydrophobic polymer film according to any one of claims 3 to 9; Preferably, the superhydrophobic polymer membrane is used in oil-water separation in the purification of ECH methanol distillation wastewater.

Citation Information

Patent Citations

  • Process for the separation of epoxychloropropane

    CN101293882A